ANALISIS SURVEY KEPUASAN MASYARAKAT DALAM PENERAPAN INOVASI LESEHAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMBAWA BARAT - RUDI, RUDI; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; UMAR, UMAR (Universitas Mahasaraswati K. Mataram, 2023)
This research aims to determine the effectiveness and level of community satisfaction in implementing Smart Era Service Innovations through villages/sub-districts (LESEHAN. This research method uses mixed methods research with qualitative and quantitative approaches, the location or place of this research was carried out at the Population and Civil Registration Service (Dukcapil) of West Sumbawa Regency. The data collection technique used was the questionnaire, interview, observation, informant, event, documentation method. Meanwhile, to obtain more accurate data, data analysis is used, namely carrying out Validity and Reliability Tests, Classical Assumption Tests and Hypothesis Tests. The research results are the use of the Salam Dukcapil application, which is a web-based application accessed via a link by Village and Subdistrict Operators https://salamdukcapilksb.id/login_operator. People come to the village or sub-district office according to their domicile with the requirements which will be processed and sent to Dukcapil by the village operator via the Salam Dukcapil application. Officers at Dukcapil will receive the proposal file via the Salam Dukcapil application. Then they will check, verify and process the file after the documents are complete. , then the officer will send it back to the village. The village will print the document and hand it over to the community receiving the service. The results of the validity and reality tests show that the overall data is valid, but based on the results of the hypothesis test via the T test, the values for the five variables are greater than t table with α 0.05% (dk= N – 2 = 156 – 2) = 1.655, which means H1 : P yx1 ≠ 0 (H1 is accepted, Ho is rejected). The consequence of accepting H1 means that 5 variables have a significant influence on Community Satisfaction with the Implementation of LESEHAN Innovation at the West Sumbawa Regency Population and Civil Registration Service. The effectiveness of using the Salam Dukcapil application in implementing Lesehan innovation has been running effectively. The final conclusion is that by wanting to use 5 indicators, namely requirements, system, time, performance and facilities and infrastructure, the community will be able to understand the characteristics of the country and civil registration will be greatly facilitated through the innovation of village/kelurahan Era Smart Services (LESEHAN).